2019
DOI: 10.3390/agronomy9120805
|View full text |Cite
|
Sign up to set email alerts
|

Nutraceutical Uses of Traditional Leafy Vegetables and Transmission of Local Knowledge from Parents to Children in Southern Benin

Abstract: This study assessed differences on the uses and transmission of traditional knowledge (TK) about three traditional leafy vegetables (Crassocephalum crepidioides (Juss. ex Jacq.) S. Moor, Launaea taraxacifolia (Willd.) Amin ex C. Jeffrey, and Vernonia amygdalina Del.) of the Asteraceae family over two generations in three villages: Adjohoun, Dangbo, and Pobè (southern Benin). Individual semi-structured ethnobotanical interviews of 360 respondents were conducted in the villages with young girls, boys, and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…The three clusters related to the ranking of the uses of spider plants suggested that sociolinguistic groups close to each other were more likely to rank the utilization traits in a similar way, which could imply that the clustered groups shared similar cultural beliefs. This observation is consistent with the findings of other researchers [44][45][46], who found that traditional knowledge on the use of indigenous vegetables was more likely to be passed on amongst relations. In this study, sociolinguistic groups from Omusati formed the first cluster, Ohangwena, Oshana and Oshikoto formed the second cluster, while the third cluster comprised sociolinguistic groups from Okavango West.…”
Section: Discussionsupporting
confidence: 93%
“…The three clusters related to the ranking of the uses of spider plants suggested that sociolinguistic groups close to each other were more likely to rank the utilization traits in a similar way, which could imply that the clustered groups shared similar cultural beliefs. This observation is consistent with the findings of other researchers [44][45][46], who found that traditional knowledge on the use of indigenous vegetables was more likely to be passed on amongst relations. In this study, sociolinguistic groups from Omusati formed the first cluster, Ohangwena, Oshana and Oshikoto formed the second cluster, while the third cluster comprised sociolinguistic groups from Okavango West.…”
Section: Discussionsupporting
confidence: 93%
“…For the ethnobotanical analysis, indices such as the total use value (UVTotal), food use value (UVFood), medicinal use value (UVMed), social use value (UVSoc), cultural worship (UVCc), plant part use value (PPUV) and fidelity level (FL) were computed. The indices related to the use value (UV) and PPUV were computed following the formulas used by Akakpo and Achigan-Dako (2019); the FL was computed following the formula used by Ugulu (2012).…”
Section: Methodsmentioning
confidence: 99%
“…2 c) are commonly used fresh or dried for the preparation of sauces, soups and stews due to their purported health benefits [ [55] , [56] , [57] , [58] ]. Particularly in Benin, C. rubens and C. crepidioides (popularly called “Gbolo”) are used as traditional leafy vegetables in sauces as they are believed to treat malaria, fever and indigestion [ 59 , 60 ]. Similarly, in Nigeria, the leaves and stems of C. rubens and C. crepidioides (popularly called “Ebolo”) are commonly consumed as vegetable in soups or sauces and for medicinal purposes [ 61 ].…”
Section: Current Trends In Pa Contamination Of Foodstuffs In Africamentioning
confidence: 99%